Testing for convergence and catching-up for Kedah with the rest of the states in Malaysia: a panel unit root test analysis - Habibullah, Muzafar Shah; Awang Marikan, Dayang Affizah; Lim, Kian Ping; Puah, Chin Hong (IUP Publications, 2009)
In Malaysia, the issue of economic convergence is much debated. Despite various Malaysia Development Plans for the past three decades, regional disparity among states persists. Therefore, the objective of the present paper is to address the question whether the state of Kedah has been converging, catching up or falling behind other states in Malaysia. The panel unit root test results, obtained using the annual data for the period 1961-2003, suggest that the state of Kedah has been catching-up with other states. In this respect, the local government has an important role to play in enhancing the growth by continuously providing stable economic environment for investment and other productive economic activities.